Comparison of hemagglutination inhibition and hemagglutinin pseudovirus neutralization titres in relation to protection against influenza in a mouse model. (11th June 2021) - Huang, Y.; Lin, Z.; Wang, W.; Weiss, C.; Xie, H.; Forshee, R.A.
Abstract: The hemagglutination inhibition (HI) test has long been used as a standard measure of antibody response for inactivated influenza vaccines. However, the HI test has limitations, such as insensitivity when using some H3N2 virus strains and failure to detect neutralizing antibodies that target regions distant from the receptor binding site. We therefore examined a hemagglutinin pseudovirus neutralization (PVN) test as a possible supplement or alternative to the HI test. We evaluated the association of HI or PVN titres with protection against influenza infection in mice based on morbidity (where the illness was defined as 25% body weight loss). We assessed this relationship using dose–response models incorporating HI or PVN titres as a variable. The morbidity was correlated with the pre‐exposure titres, and such a correlation was well described by a modified dose–response model. The mathematical modelling suggests that PVN titres consistently show a stronger association with in vivo protection as compared to HI titres in mice. Given our findings, the PVN test warrants further investigation as a tool for evaluating antibody responses to influenza vaccines containing hemagglutinin. The resulting models may also be useful for analyzing human clinical data to identify potentially protective antibody titres against influenza illness. Abstract : Significance and Impact of the Study: This is the first study that applied a mechanistic computational model to quantify and compare the correlation of hemagglutination inhibition (HI) or hemagglutinin pseudovirus (PVN) titres with the host postinfection response using well‐controlled animal laboratory data. The results show clear advantages of PVN titre over HI titre for evaluation of postinfection response against influenza. These findings may assist evaluations of antibody responses elicited by influenza vaccines.